Immunostimulatory properties and antitumor activities of glucans (Review) - Vannucci, Luca; Krizan, Jiri; Sima, Petr; Stakheev, Dmitry; Caja, Fabian; Rajsiglova, Lenka; Horak, Vratislav; Saieh, Mustafa (International journal of oncology, 2013)
New foods and natural biological modulators have recently become of scientific interest in the investigation of the value of traditional medical therapeutics. Glucans have an important part in this renewed interest. These fungal wall components are claimed to be useful for various medical purposes and they are obtained from medicinal mushrooms commonly used in traditional Oriental medicine. The immunotherapeutic properties of fungi extracts have been reported, including the enhancement of anticancer immunity responses. These properties are principally related to the stimulation of cells of the innate immune system. The discovery of specific receptors for glucans on dendritic cells (dectin-1), as well as interactions with other receptors, mainly expressed by innate immune cells (e.g., Toll-like receptors, complement receptor-3), have raised new attention toward these products as suitable therapeutic agents. We briefly review the characteristics of the glucans from mycelial walls as modulators of the immunity and their possible use as antitumor treatments.
Keywords: Animals; přirozená imunita; beta-glukany; makrofágy; Lectins, C-Type; Dendritic Cells; Adjuvants, Immunologic; dendritické buňky; lidé; Antineoplastic Agents; Macrophages; protinádorové látky; Mice; lektiny typu C; signální transdukce; myši; Signal Transduction; Medicine, East Asian Traditional; tradiční orientální medicína; beta-Glucans; Cell Extracts; Immunity, Innate; Agaricales; zvířata; adjuvancia imunologická; buněčné extrakty; Humans